IL-18/IL-15/IL-12 synergy induces elevated and prolonged IFN-γ production by ex vivo expanded NK cells which is not due to enhanced STAT4 activation. (August 2017) - Lusty, Evan; Poznanski, Sophie M.; Kwofie, Karen; Mandur, Talveer S.; Lee, Dean A.; Richards, Carl D.; Ashkar, Ali A.
Highlights: Expanded NK cells respond to IL18/IL12 with robust IFNγ and TNFα production. NK cells maintain elevated IFNγ production but not TNFα after removal of IL18/IL12. IL18/IL12 induces unique IFNγ + population distinct from unstimulated IFNγ + NK cells. IL18/IL12 induction and maintenance of IFNγ is not due to enhanced STAT4 activity. Elevated and prolonged IFNγ production is mediated by up-regulation of IFNγ mRNA. Abstract: The synergistic effect of IL-18/IL-15/IL-12 stimulation potently activates NK cells, inducing high levels of IFN-γ production. As a result of this potent stimulatory effect, NK cell pre-activation with IL-18/IL-15/IL-12 is being developed as a cancer immunotherapy. Ex vivo expansion of NK cells enables the efficient generation of large numbers of NK cells for wide-scale and repeated therapeutic use, and is thus an important source of NK cells for clinical application. However, the effects of IL-18/IL-15/IL-12 stimulation on ex vivo expanded NK cells have not yet been assessed. Thus, the present study assessed the effects of IL-18/IL-15/IL-12 stimulation on NK cells expanded ex vivo using K562-based artificial antigen presenting cells expressing membrane-bound IL-21. We report that ex vivo expanded NK cells stimulated with IL-18/IL-15/IL-12 produce high levels of IFN-γ and TNFα, have potent cytotoxicity, and maintain prolonged IFN-γ production following removal of stimulation. IL-18/IL-15/IL-12 stimulation induces a phenotypically unique IFN-γ-producing population with reduced CD16 expression and greater CD25 expression as compared to stimulated IFN-γ- NK cells and unstimulated NK cells. We elucidate that the mechanism of synergy for induction and maintenance of IFN-γ production is not due to a further enhancement of STAT4 activation compared to stimulation with IL-12 alone. Furthermore, we demonstrate that the synergistic increase in IFN-γ is not solely under translational regulation, as elevated levels of IFN-γ mRNA contribute to the synergistic increase in IFN-γ. Overall, this study characterizes the response of ex vivo expanded NK cells to IL-18/IL-15/IL-12 stimulation and supports the use of ex vivo expanded NK cells as a feasible and efficient source of IL-18/IL-15/IL-12 pre-activated NK cells for adoptive transfer in cancer immunotherapies.